Outcome of assisted reproductive technology in women with poor ovarian response undergoing infertility treatment in the reproductive medicine unit of Groote Schuur hospital: a five-year review - Senaya, Charles M (Department of Obstetrics and Gynaecology, 2021)
Background: Poor response of the ovaries to gonadotropin stimulation is associated with poor outcome following in vitro fertilization. The historical lack of a standard definition for poor ovarian response has resulted in a wide variation in prevalence and outcome measures. More recently, the Bologna criteria has emerged as the standard for identification of poor ovarian responders. There is paucity of literature on poor ovarian response in the African setting. This study was conducted to document the prevalence and the outcome of in vitro fertilization among poor ovarian responders in women undergoing assisted reproduction technology in the public sector of Western Cape Province of South Africa. Method: Retrospective review of data of women who underwent assisted reproduction technology between January 2011 and December 2015 was conducted. The Bologna criteria was used to identify women for inclusion into the study. For the analysis of prevalence and treatment outcomes, only a woman's first cycle at the Groote Schuur Hospital was included, however the occurrence of further cycles was recorded. Main results: A total of 40 women met the criteria for poor ovarian response in this study. The prevalence of poor ovarian response was 3.6%. The mean age among the study population was 37.8years (25 – 42yrs). Cycle cancellation rate due to poor ovarian response was 15.0% and the average number of eggs retrieved was 1.8. Twenty-four (60%) women had at least one embryo transferred. The clinical pregnancy and live birth rates were 10.0% and 5.0% respectively, per cycle initiated. Half of those with failed IVF due to poor ovarian response withdrew from the program. Conclusion: The prevalence of poor ovarian response among women who underwent assisted reproduction at Groote Schuur Hospital was 3.6% which is low compared to 9-24% reported in other studies. The clinical pregnancy and live birth rates were low. Half of the women did not continue with treatment after their first failed IVF cycle.